On the negative social effects of exaggerated distrust and paranoid cognition - González-Fernández, Rodrigo (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2022)
In view of Kramer’s theory about paranoid cognition, this paper examines how exaggerated distrust and such cognition produce important negative effects upon social reality. The first section deals with Searle’s theory of social reality, and how it is basically explained in terms of one world of physical particles and groups of intentional agents performing “we” actions. The aim of this section is to show that the “we” actions of collective intentionality allow fundamental social practices, namely, those related to institutions. Looking at trust, cooperation, and collective intentionality, the second section examines in what sense these three elements form the triad of human civilization. Finally, the last section analyses which negative effects exaggerated distrust and Kramer’s paranoid cognition have upon the Searlean social reality: both, which break off cooperative relations and solemn pacts, end up disrupting the triad.